Musical code and musical ecfrasis in the novel by I. Franco “William Tell” - Каленіченко, Ольга (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article analyzes the novel by I. Franco “William Tell” through the prism of musical code and musical ecfrasis. So far, none of the French scholars has paid attention to the plot-forming role of the Rossini’s opera in the short story, but in the first part of the four-part short story the young couple is going to the opera, in the following parts Franco gradually reveals the heroine’s perception of the overture to the opera, and then its individual scenes. After the end of the opera, Olya novelistically unexpectedly, on the external-eventual plane of the novel, declares that she is not in love with Volodko, but on the internal, spiritual and psychological - thanks to the verbal description of the music and its perception by the heroes - this becomes natural. With the help of musical ecfrasis, the depth of Olya’s impression of the Rossini’s opera and the heroine’s psychological sensitivity to what she heard become clear. Moreover, Franco finds his “niche” in the image of the heroine’s understanding of opera music: while foreign writers of the mid-19th century most often describe the feelings and emotions that heroes evoke in music, Franco, relying on picture programmability (landscapes of his native land and ideal representations of the heroine about family happiness), which Olya accompanies the heard music, reveals the rich inner world of the girl and her ideals. Rossini’s romantic heroic-patriotic opera “Wilhelm Tell”, her musical images and stage performance become a litmus test in the novel: the relationship of the characters to the opera performance, impressions of it become an important way of revealing their characters. Volodka’s superficial attitude to music as entertainment, on the one hand, and Olya’s ability under the influence of music to see the true meaning of life, correcting her worldview from pastorally romantic to heroic-romantic, on the other hand, make it possible to understand the different life positions of the heroes - the intellectual adaptive Volodka’s service to the people of Olya, and, in fact, the ideological and artistic concept of the writer himself.